Virtual reality-based vestibular rehabilitation therapy: a scoping review - Megat Abdul Karim @ Rosmady, Megat Ikmal; Mohd Sakeri, Nurul Syarida; Jamaluddin, Saiful Adli (IIUM Press, 2025)
Virtual reality (VR) technologies have been increasingly developed to support vestibular rehabilitation therapy by providing immersive and interactive environments that enhance patient engagement, improve therapeutic outcomes while ensuring patient safety.This scoping review aims to identify and compare the various types of VR-based vestibular rehabilitation approaches currently available. Methods: A scoping review was conducted following the Joanna Briggs Institute (JBI) framework to explore and compare distinct VR-based vestibular rehabilitation methods. Studies were included if they utilized VR in vestibular rehabilitation, were published in English between 2012 and 2022, and were available in full text. Searches were performed across electronic databases including PubMed, ScienceDirect, and ProQuest. Relevant data from the selected studies were summarized descriptively. Results: A total of nine studies met the inclusion criteria, comprising one observational study and eight experimental studies. Three primary categories of VR devices were identified: head-mounted displays, force plate systems, and hybrid VR setups. These devices were used to deliver vestibular rehabilitation interventions across various protocols and settings. Conclusion: All included studies reported that VR-based vestibular rehabilitation was effective and well-tolerated, despite notable differences in intervention procedures and outcome assessments. A systematic review is recommended to further evaluate the comparative effectiveness of VR-based versus conventional vestibular rehabilitation therapies.